Cargo proteins in extracellular vesicles: potential for novel therapeutics in non-alcoholic steatohepatitis - Jimin Kim; Seul Ki Lee; Seon-Yeong Jeong; Hye Jin Cho; Joonghoon Park; Tae Min Kim; Soo Kim (Journal of Nanobiotechnology, 2021)
Abstract Background Extracellular vesicles (EVs) are recognized as novel cell-free therapeutics. Non-alcoholic steatohepatitis (NASH) remains a critical health problem. Herein, we show that EVs from pan peroxisome proliferator-activated receptor agonist-primed induced mesenchymal stem cell (pan PPAR-iMSC-EVs) has unique cargo protein signatures, and demonstrate its therapeutic function in NASH. Results A unique protein signatures were identified in pan PPAR-iMSC-EVs against those from non-stimulated iMSC-EVs. NASH mice receiving pan PPAR-iMSC-EVs showed reduced steatotic changes and ameliorated ER stress and mitochondiral oxidative stress induced by inflammation. Moreover, pan PPAR-iMSC-EVs promoted liver regeneration via inhibiting apoptosis and enhancing proliferation. Conclusions We conclude that our strategy for enriching unique cargo proteins in EVs may facilitate the development of novel therapeutic option for NASH. Graphical Abstract